Mulberry branch fiber improved lipid metabolism and egg yolk fatty acid composition of laying hens via the enterohepatic axis - Hong Hu; Anjian Li; Changyou Shi; Liang Chen; Zelong Zhao; Xiaojian Yin; Qiang Zhang; Ying Huang; Hongbin Pan (Microbiome, 2024)
Abstract Background The utilization of mulberry branch fiber (MF), the largest by-product of the sericulture industry, is an important issue. Supplementation with MF as a dietary fiber for poultry may serve as a useful application. However, little is known about the effects of MF on liver lipid metabolism and egg yolk fatty acid composition of laying hens and their underlying mechanisms. In this study, we performed a multi-omics investigation to explore the variations in liver lipid metabolism, egg yolk fatty acid composition, gut microbiota, and the associations among them induced by dietary MF in laying hens. Results Dietary MF had no harmful effects on the laying performance or egg quality in laying hens. The enzyme activities associated with lipid metabolism in the liver were altered by the addition of 5% MF, resulting in reduced liver fat accumulation. Furthermore, dietary 5% MF induced the variation in the fatty acid profiles of egg yolk, and increased the polyunsaturated fatty acid (PUFA) content. We observed a significant reduction in the diversity of both gut bacteria and changes in their compositions after the addition of MF. Dietary MF significantly increased the abundance of genes involved in fatty acid biodegradation, and short-chain fatty acids biosynthesis in the gut microbiota of laying hens. The significant correlations were observed between the liver lipid metabolism enzyme activities of hepatic lipase, lipoprotein lipase, and total esterase with gut microbiota, including negative correlations with gut microbiota diversity, and multiple correlations with gut bacteria and viruses. Moreover, various correlations between the contents of PUFAs and monounsaturated fatty acids in egg yolk with the gut microbiota were obtained. Based on partial-least-squares path modeling integrated with the multi-omics datasets, we deduced the direct effects of liver enzyme activities and gut bacterial compositions on liver fat content and the roles of liver enzyme activities and gut bacterial diversity on egg yolk fatty acid composition. Conclusions The results indicate that dietary MF is beneficial to laying hens as it reduces the liver fat and improves egg yolk fatty acid composition through the enterohepatic axis. Video Abstract Graphical Abstract